Arms control and disarmament law - Casey-Maslen, Stuart (Oxford, United Kingdom ; New York, NY : Oxford University Press, 2021)
"In seven concise chapters, he traces the history of arms control and disarmament in the modern era, addressing the issues surrounding biological and chemical weapons, the non-proliferation of nuclear weapons, and conventional weapon and arms transfer regimes. He concludes by considering how, in order to remain relevant, disarmament and arms control will need to adapt to rapidly evolving technologies that defy traditional means of verification and control"--Publisher's description.
Key components of arms control and disarmament -- Biological and chemical weapons -- Nuclear weapons and nuclear weapon regimes -- Conventional weapon regimes -- Arms transfer regimes -- Verification of arms control and disarmament agreements -- Future of arms control and disarmament.
Includes bibliographical references and index.
Keywords: Arms control; Disarmament; Military weapons (International law)